Tumbuhan Rempah dan Masakan Tradisional di Kelurahan Nanggewer Mekar, Cibinong, Kabupaten Bogor - marwan setiawan; Mulyati Rahayu; Dewi Qurrohta Wahyu Ningsih; Nissa Arifa (Jurnal Masyarakat dan Budaya, 2021)
Indonesia has diversity of ethnics with various cultural patterns, traditional knowledge and cultural differences, it makes Indonesia become a country with the most cultures in the world. Traditional cuisine is a dish that is consumed from generation to generation with various spices. Traditional cuisine are foods and dishes that have been consumed for many generations. Biodiversity in Indonesia was a source of commercial commodities in the past, that attracted traders, including spices. This research was conducted in Nanggewer Mekar, Cibinong, Bogor. The majority of people are Sundanese, besides Javanese and Betawi. The traditional cuisine found in Nanggewer Mekar, using a lot of spices that can characterize their dish. The spice plants were used for traditional cuisine around 23 species (19 genus and 14 family). The traditional cuisine include: laksa, soto betawi, semur jengkol and served on certain occasions.